2020
DOI: 10.3389/fncom.2020.554186
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Antidepressant Citalopram Treatment Response via Changes in Brain Functional Connectivity After Acute Intravenous Challenge

Abstract: Introduction: The early and therapy-specific prediction of treatment success in major depressive disorder is of paramount importance due to high lifetime prevalence, and heterogeneity of response to standard medication and symptom expression. Hence, this study assessed the predictability of long-term antidepressant effects of escitalopram based on the short-term influence of citalopram on functional connectivity. Methods: Twenty nine subjects suffering from major depression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…A large study employing NBS found the DMN was the primary distinguisher between remitters and non-remitters with the following associated with remission: greater within DMN connectivity, greater connectivity between the DMN, FPN, and SMN, greater connectivity between the DMN and visual, limbic, auditory and VAN, and greater connectivity between the FPN/SMN and C-ON/dorsal attention network ( Korgaonkar et al, 2020 ). Another study employing NBS noted that the DMN, VAN, and FPN were the primary predictors remission and response, though the method precluded an overall directionality of the effect ( Klöbl, 2020 ). A large study investigating intra- and inter-network connectivity strength reported that greater internal DMN connectivity and lower external ECN connectivity predicted symptom improvement ( Fan et al, 2020 ).…”
Section: Functional Predictorsmentioning
confidence: 99%
“…A large study employing NBS found the DMN was the primary distinguisher between remitters and non-remitters with the following associated with remission: greater within DMN connectivity, greater connectivity between the DMN, FPN, and SMN, greater connectivity between the DMN and visual, limbic, auditory and VAN, and greater connectivity between the FPN/SMN and C-ON/dorsal attention network ( Korgaonkar et al, 2020 ). Another study employing NBS noted that the DMN, VAN, and FPN were the primary predictors remission and response, though the method precluded an overall directionality of the effect ( Klöbl, 2020 ). A large study investigating intra- and inter-network connectivity strength reported that greater internal DMN connectivity and lower external ECN connectivity predicted symptom improvement ( Fan et al, 2020 ).…”
Section: Functional Predictorsmentioning
confidence: 99%
“…Improved predictive accuracy observed in the delta models, which include imaging data for each patient from two separate timepoints, requires yet additional resources. Results from Klöbl et al (2020) , however, suggest medication-induced FC alterations may be achieved in a much shorter timeframe by an acute intravenous SSRI challenge. This may allow the week 2 timepoint used in delta models to be acquired at the baseline visit following an intravenous challenge, eliminating the need for a second scanning session and 2-week medication trial before response prediction can be made.…”
Section: Discussionmentioning
confidence: 93%
“…fMRI preprocessing and filtering fMRI data were preprocessed in SPM12 and ArtRepair toolbox 36 , following an established protocol 37 . In brief, the data underwent correction for transient slice artifacts and slice-timing discrepancies, followed by realignment and reslicing of the realigned images.…”
Section: Data Acquisitionmentioning
confidence: 99%